Skuteczne delegowanie zadań : poradnik dla lidera - Turregano, Clemson (Report (Center for Creative Leadership)., 2019)
This guidebook outlines the benefits of effective delegation and the fears and concerns that can prevent or hinder it, then offers four key ideas that leaders can use to enable better delegation.